2021
DOI: 10.3389/fimmu.2021.633540
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Reduces Neutrophil Migration and Increases Susceptibility to Sepsis in Diabetic Mice

Abstract: Sepsis is one of the most common comorbidities observed in diabetic patients, associated with a deficient innate immune response. Recently, we have shown that glucagon possesses anti-inflammatory properties. In this study, we investigated if hyperglucagonemia triggered by diabetes might reduce the migration of neutrophils, increasing sepsis susceptibility. 21 days after diabetes induction by intravenous injection of alloxan, we induced moderate sepsis in Swiss-Webster mice through cecum ligation and puncture (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…It is argued that a hyperglycemic environment may impair the function of neutrophils and monocytes and increase susceptibility to certain organisms. 8,9 A Danish retrospective study involving 1318 adult CAP patients reported that in subjects without diabetes metabolism, a higher blood glucose level was an independent predictor for intensive care unit (ICU) admission (OR=1.25, 95% CI 1.13-1.39). 10 Multivariate logistic regression analysis in a Chinese retrospective study showed that a higher admission blood glucose level was significantly associated with the 30-day all-cause mortality (OR=1.91, 95% CI:…”
Section: Discussionmentioning
confidence: 99%
“…It is argued that a hyperglycemic environment may impair the function of neutrophils and monocytes and increase susceptibility to certain organisms. 8,9 A Danish retrospective study involving 1318 adult CAP patients reported that in subjects without diabetes metabolism, a higher blood glucose level was an independent predictor for intensive care unit (ICU) admission (OR=1.25, 95% CI 1.13-1.39). 10 Multivariate logistic regression analysis in a Chinese retrospective study showed that a higher admission blood glucose level was significantly associated with the 30-day all-cause mortality (OR=1.91, 95% CI:…”
Section: Discussionmentioning
confidence: 99%
“…Male Swiss-Webster mice (5-6 weeks old with 20 to 25g) were obtained from Oswaldo Cruz Foundation breeding colony and used in accordance with the guidelines of the Committee on Use of Laboratory Animals of Oswaldo Cruz Institute (CEUA-IOC/Fiocruz, license L-027/2016). Diabetes was randomly and blinded designated induced in 12 hours fasted mice (water ad libitum ) by a single intravenous injection of alloxan monohydrate (65 mg/kg) ( 20 ) diluted with sterile saline (0.9% NaCl). Only mice showing two successive determinations of blood glucose levels (3 and 7 days after alloxan injection) greater than 16.7 mmol/L were considered diabetic and included in the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…All solutions were prepared immediately before use. blinded designated induced in 12 hours fasted mice (water ad libitum) by a single intravenous injection of alloxan monohydrate (65 mg/kg) (20) diluted with sterile saline (0.9% NaCl). Only mice showing two successive determinations of blood glucose levels (3 and 7 days after alloxan injection) greater than 16.7 mmol/L were considered diabetic and included in the experiment.…”
Section: Chemicalsmentioning
confidence: 99%
“…Under normal physiological conditions, the intestine has a regulatory effect on kidney function, including neuroendocrine involvement. For example, glucagon-like peptide-1 (GLP-1) ( Wu et al., 2021a ; Zhuang et al., 2021 ), guanosine ( Estaki et al., 2014 ), glucagon ( Müller et al., 2020 ; Insuela et al., 2021 ), vasoactive intestinal peptide ( Song et al., 2021 ), polypeptide ( Qi et al., 2021 ), gastrin ( Stewart et al., 2020 ) and other intestinal factors can regulate renal dysfunction. Pathological conditions, due to dietary restrictions and gastrointestinal, most of the patients in the gut microbial metabolism, which is mainly composed of protein hydrolysis into fermentation mode, the end product of protein by the metabolism of gut microbes such as phenol, indole are the endotoxin source of uremia, such as its nephrotoxicity and vascular toxicity has been confirmed that many clinical research institute ( Ondrussek-Sekac et al., 2021 ).…”
Section: Gut-kidney Axismentioning
confidence: 99%